Improvement in agroforestry system - Sarkar, Pradip Kumar; Bishnoi, Santosh K.; Shinde, Reshma; Das, Bikash (Indian Farming, 2018)
The monetary gain from traditional agroforestry systems need to be highlighted for attracting smalland marginal-farmers for adoption of agroforestry along with the improved technology for sustainability. However, the ecosystem services of different perennial species have already been established. In this context, species with short gestation period should find a prominent place in different agroforestry systems in Jharkhand. Hence, there is an urgent need for strengthening research effort in identifying improved and qualitative planting stocks of suitable agroforestry species for the state. Strengthening of nursery programme for large-scale availability of quality planting materials of perennial trees can go a long way in rapid expansion of area under agroforestry systems in Jharkhand.